High-gloss double-85-resistant efficient flame-retardant nylon composite material as well as preparation method and application thereof

By introducing components such as PA66, semi-aromatic nylon, glass fiber, etc. into the nylon 6 composite material, and using technical means such as collaborative flame retardant and chain extension reaction, the shortcomings of nylon 6 composite material in terms of mechanical strength and flame retardant properties are solved, and high-gloss nylon composite material with high efficiency flame retardant and mechanical strength are achieved, which is suitable for electronic and electrical appliance fields.

CN119798972APending Publication Date: 2025-04-11HUBEI HEJU POLYMER MATERIAL CO LTD

Patent Information

Application Number
CN202411913573.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing nylon 6 plastics have shortcomings in terms of mechanical strength and flame retardant properties, and the introduction of halogen-free flame retardant will lead to poor injection molding fluidity, white appearance, severe floating fibers, decreased mechanical strength and improved water absorption rate of the composite.

Method used

High-efficiency flame-retardant nylon composite material with high gloss and double-resistant 85 is adopted. By introducing PA66, semi-aromatic nylon, glass fiber, halogen-free flame retardant, synergistic flame retardant, chain extender and mold release agent into the PA6 system, combined with synergistic flame retardant, chain extension reaction, surface infiltration, heterophase nucleation and physical shear of glass fibers, flame retardant efficiency and mechanical properties are improved.

Benefits of technology

It has achieved high-efficiency flame retardant (UL-94V0) and high-gloss nylon composite material with good aging resistance, processing fluidity and appearance finish, and is suitable for electronic and electrical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798972A_ABST
    Figure CN119798972A_ABST
Patent Text Reader

Abstract

The invention discloses a high-gloss double-85-resistant efficient flame-retardant nylon composite material as well as a preparation method and application of the high-gloss double-85-resistant efficient flame-retardant nylon composite material. The high-efficiency flame-retardant nylon composite material comprises the following components: 40%-80% of PA6 nylon, 2%-10% of PA66 nylon, 2%-10% of semi-aromatic nylon, 5%-50% of glass fibers, 8%-20% of a halogen-free flame retardant, 1%-10% of a synergistic flame retardant, 0.2%-5% of a chain extender, 0.2%-1% of a release agent and 0.2%-1% of a nucleating agent. The efficient flame-retardant nylon composite material disclosed by the invention has the characteristics of high flame-retardant efficiency (UL-94V0), good mechanical strength, smooth surface appearance, hot and humid environment resistance, low precipitation and the like, and is suitable for the field of electronic appliances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-gloss, double 85-resistant, efficient flame-retardant nylon composite material and a preparation method and application thereof. Background Art

[0002] Nylon 6 (PA6) is an important engineering plastic with the characteristics of thermoplasticity, light weight, good toughness, chemical resistance and durability. It is mostly used in automotive parts, engineering accessories, mechanical parts, electronic appliances and other products. However, its notch impact strength is low and it is a highly flammable product. In addition, glass fiber reinforced PA6 has a "burning core effect", which greatly limits its scope of use.

[0003] At present, the mechanical strength of PA6 is mainly improved by introducing glass fiber, and the high flammability problem of PA6 is improved by introducing halogen-free flame retardant organic phosphite. However, it is often necessary to add a large amount of flame retardant additives such as patent CN104448801A, which leads to poor injection fluidity of composite materials, whitish injection appearance, severe floating fibers, decreased mechanical strength, increased water absorption, or reduced nylon resin content such as patent CN118374147A. The maximum proportion of nylon is ≤50 parts, of which 5-15 parts are aromatic nylon with high carbon content, which greatly increases the cost and has severe floating fibers.

[0004] The dispersion and compatibility of flame retardants in materials are improved by using additives such as reactive compatibilizers such as diisocyanates, and the amount of organic phosphinates used and the side effects on appearance are improved, such as patent CN109552968A. However, due to the large amount of diisocyanates or oxides (initiators) added, aging may be accelerated.

[0005] In view of the low flame retardant efficiency caused by the poor dispersion of the above halogen-free flame retardants, and the large dosage of halogen-free flame retardants will reduce the mechanical, appearance and anti-aging properties of composite materials, the development of processing aids with synergistic flame retardancy, chain extension enhancement and smooth surface to improve the flame retardant efficiency (flame retardant content ≤ 10wt%) and increase the aliphatic nylon resin content (aliphatic nylon resin content ≥ 70%) of halogen-free flame retardant composite materials is the current research focus. Summary of the invention

[0006] Based on the deficiencies in the prior art, the purpose of the present invention is to provide a high-gloss, double 85-resistant, efficient flame-retardant nylon composite material and a preparation method and application thereof. The efficient flame-retardant nylon composite material has the characteristics of high flame retardant efficiency (UL-94V0), good mechanical strength, smooth surface appearance, resistance to wet and hot environments, low precipitation, etc., and is suitable for the field of electronic appliances.

[0007] In order to achieve the above purpose, this application adopts the following technical solutions:

[0008] In the first aspect, the present invention provides a high-gloss, double-85 resistant, efficient flame-retardant nylon composite material, which comprises the following components by weight percentage: 40-80% PA6 nylon, 2-10% PA66 nylon, 2-10% semi-aromatic nylon, 5-50% glass fiber, 8-20% halogen-free flame retardant, 1-10% synergistic flame retardant, 0.2-5% chain extender, 0.2-1% release agent, and 0.2-1% nucleating agent.

[0009] In the above technical solution, the halogen-free flame retardant is a mixture of organic phosphinates and their derivatives, melamine derivatives, and zinc borate, accounting for 8-20%, 0-7%, and 0-7% of the total weight of the composite material, respectively.

[0010] In the above technical solution, the semi-aromatic nylon is PA6T / 6I / 66 or MXD6.

[0011] High molecular weight PA6T / 6I / 66 or MXD6 resin is easier to form carbon when burning, and it is easy to isolate oxygen between the inside and outside of the composite material. The inventors found through a large number of experiments that PA6T / 6I / 66 or MXD6 resin has good carbonization and flame retardant effects.

[0012] The viscosity of PA6T / 6I / 66 or MXD6 resin measured according to ISO 307 standard is 0.5-3.0, the test temperature is 25℃, the terminal amine content is 30-80mmol / kg, and the sample with a resin concentration of 0.005g / ml is dissolved in 96% concentrated sulfuric acid and measured with an Ubbelohde viscometer.

[0013] In the above technical solution, the high-efficiency flame-retardant nylon composite material further comprises 0.5-4% of processing aids, and the processing aids comprise antioxidants and lubricants.

[0014] Preferably, the mass ratio of antioxidant to lubricant is 4:5. Antioxidant and lubricant are conventional commercial reagents. As one embodiment, the antioxidant is at least one of hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, etc. The lubricant is at least one of pentaerythritol stearate, silicone, polyethylene wax, etc.

[0015] In the above technical solution, the synergistic flame retardant is a polyacrylic acid-modified MXD6 synergistic flame retardant, and its preparation method comprises the following steps:

[0016] S1: preparing a polyacrylic acid solution: adding 40-80% m-xylylenediamine and 10-20% acrylic acid to a reaction kettle equipped with a stirring and condensation reflux device, placing the kettle in a constant temperature oil bath and heating the temperature to 120°C, dissolving 0.1-5% benzoyl peroxide in 5-20% xylene, and dripping the mixture into the reaction kettle. After a certain reaction time, changing the condensation reflux to condensation recovery, using the difference in boiling points to evaporate the xylene, and recycling it, finally obtaining a low molecular weight polyacrylic acid / m-xylylenediamine solution;

[0017] S2: Preparation of polyacrylic acid modified MXD6: Prepare 30-50wt% adipic acid suspension A and 60-80wt% meta-phenylenediamine solution B respectively; obtain 40-60% carboxylic acid terminated intermediate ABA solution and 40-60% amine terminated intermediate BAB solution respectively in different dropwise addition orders; add the ABA solution into a reaction kettle with a stirring paddle, dropwise add the BAB solution into the ABA solution under stirring at 80°C, and add 1-10% low molecular weight polyacrylic acid / meta-phenylenediamine solution; The dimethylamine solution is adjusted to pH 7.0-7.5 by adding meta-phenylenediamine to finally complete the reaction; MXD6 salt is configured into a 60-90wt% aqueous solution and put into a reactor, and the temperature is slowly raised to 210°C under a N2 atmosphere. After the reaction is completed, the pressure is released to normal pressure, the temperature is raised to 240°C, and the pressure is evacuated and maintained between 0.07-0.03MPa, and the temperature is gradually raised to 260°C. After the reaction is completed, the material is discharged and dried at high temperature in a vacuum box to obtain a polyacrylic acid modified MXD6 synergistic flame retardant.

[0018] In the above technical solution, the chain extender is a mixture of phorone diisocyanate and polyacrylic acid modified MXD6 chain extender, wherein the percentage of phorone diisocyanate in the total weight of the composite material is 0.1-2.5%, and the preparation method of the polyacrylic acid modified MXD6 chain extender comprises the following steps:

[0019] S1: preparing a polyacrylic acid solution: adding 40-80% m-xylylenediamine and 10-20% acrylic acid to a reaction kettle equipped with a stirring and condensation reflux device, placing the kettle in a constant temperature oil bath and heating the temperature to 120°C, dissolving 0.1-5% benzoyl peroxide in 5-20% xylene, and dripping the mixture into the reaction kettle. After a certain reaction time, changing the condensation reflux to condensation recovery, using the difference in boiling points to evaporate the xylene, and recycling it, finally obtaining a low molecular weight polyacrylic acid / m-xylylenediamine solution;

[0020] S2: Preparation of polyacrylic acid modified MXD6: Prepare 30-50wt% adipic acid suspension A and 60-80wt% m-xylenediamine solution B respectively; obtain 40-60% carboxylic acid terminated intermediate ABA solution and 40-60% amine terminated intermediate BAB solution respectively in different dropwise addition orders; add the ABA solution into a reaction kettle with a stirring paddle, dropwise add the BAB solution into the ABA solution under stirring at 80°C, and add 5-20% low molecular weight polyacrylic acid / m-xylenediamine solution; The benzylenediamine solution is adjusted to pH 7.0-7.5 by adding meta-xylylenediamine to finally complete the reaction; MXD6 salt is configured into a 60-90wt% aqueous solution and put into a reactor, and the temperature is slowly raised to 210°C under a N2 atmosphere. After the reaction is completed, the pressure is released to normal pressure, the temperature is raised to 240°C, and the pressure is evacuated and maintained between 0.07-0.03MPa, and the temperature is gradually raised to 260°C. After the reaction is completed, the material is discharged and dried at high temperature in a vacuum box to obtain a polyacrylic acid modified MXD6 chain extender.

[0021] In the above technical solution, the release agent is a MXD6 release agent modified with polyacrylic acid ricinoleate, and the preparation method thereof comprises the following steps:

[0022] S1: preparing a polyacrylic acid solution: adding 40-70% ricinoleic acid and 10-20% acrylic acid to a reactor equipped with a stirring and condensation reflux device, placing the reactor in a constant temperature oil bath and heating the temperature to 120°C, dissolving 0.1-5% benzoyl peroxide in 5-20% xylene, and dripping the solution into the reactor. After a certain reaction time, changing the condensation reflux to condensation recovery, using the difference in boiling points to evaporate the xylene, and recycling it, finally obtaining a low molecular weight polyacrylic acid / ricinoleic acid solution;

[0023] S2: preparing polyacrylic acid modified ricinoleate: cooling to 85°C, adding 1-10% phorone diisocyanate, reacting under N2 atmosphere, and adjusting the viscosity of the system by adding m-xylylenediamine to finally obtain polyacrylic acid ricinoleate;

[0024] S3: Preparation of polyacrylic acid ricinoleate modified MXD6: Prepare 30-50wt% adipic acid suspension A and 60-80wt% m-xylenediamine solution B respectively; obtain 40-60% carboxylic acid terminated intermediate ABA solution and 40-60% amine terminated intermediate BAB solution respectively in different dropwise addition orders; add the ABA solution into a reaction kettle with a stirring paddle, dropwise add the BAB solution into the ABA solution under stirring at 80°C, and add 10-100% polyacrylic acid ricinoleate modified MXD6; Oleic acid ester, by adding meta-phenylenediamine to adjust the pH to 7.0-7.5, and finally complete the reaction; MXD6 salt is configured into a 60-90wt% aqueous solution and put into a reactor, and slowly heated to 210°C under N2 atmosphere. After the reaction is completed, the pressure is released to normal pressure, and the temperature is increased to 240°C, and vacuum is drawn and the pressure is maintained between 0.07-0.03MPa, and the temperature is gradually increased to 260°C. After the reaction is completed, the material is discharged and dried at high temperature in a vacuum box to obtain a polyacrylic acid ricinoleate modified MXD6 release agent.

[0025] In the present invention, PA66 resin has a heterogeneous nucleation effect in the PA6 system, which can greatly improve the crystallization temperature and crystallinity of PA6. The inventors have found through a large number of experiments that a small amount of PA66 in the PA6 system can improve the surface finish and flame retardant properties of the product.

[0026] The viscosity of PA6 measured according to ISO 307 standard is 2.4-2.6, the test temperature is 25°C, and a sample with a resin concentration of 0.005g / ml is dissolved in 96% concentrated sulfuric acid and measured with an Ubbelohde viscometer.

[0027] The synergistic flame retardant polyacrylic acid modified MXD6 compound can promote MXD6 to effectively form a carbon layer and greatly improve the flame retardant efficiency.

[0028] The chain extender polyacrylic acid-modified MXD6 compound or diisocyanate compound will react and extend the chain with PA6 during melt extrusion to form a micro-crosslinking state, thereby greatly increasing the molecular weight, improving the mechanical strength of the material, reducing the fluidity of the PA6 resin during combustion, inhibiting droplets, and improving the flame retardant effect. It will also react and extend the chain with the synergistic flame retardant polyacrylic acid-modified MXD6 compound (self-made) to form a large number of carbon layers, further improving the flame retardant effect.

[0029] The release agent MXD6 compound modified with polyacrylate castor oil can greatly improve the surface smoothness during the injection molding process, and interact with the polyacrylic acid modified MXD6 synergistic flame retardant (self-made) and polyacrylic acid modified MXD6 chain extender (self-made), further improving the carbonization efficiency of the composite material surface and improving the flame retardant effect.

[0030] The chopped length of the glass fiber is 2-10 mm and the fiber diameter is 4-15 μm.

[0031] In a second aspect, the present invention provides a method for preparing a high-gloss, double 85-resistant, high-efficiency flame-retardant nylon composite material, comprising the following steps:

[0032] S1: According to weight percentage, weigh 40-80% PA6 nylon, 2-10% PA66 nylon, 2-10% semi-aromatic nylon, 5-50% glass fiber, 8-20% halogen-free flame retardant, 1-10% synergistic flame retardant, 0.2-5% chain extender, 0.2-1% release agent, and 0.2-1% nucleating agent;

[0033] S2: pre-dry the three resins of PA6 nylon, PA66 nylon and semi-aromatic nylon in S1 respectively, and then pre-mix the glass fiber accounting for 1% to 10% of the weight percentage of the formula with PA6 nylon, PA66 nylon, semi-aromatic nylon, halogen-free flame retardant, synergistic flame retardant, chain extender, release agent and nucleating agent through a high-speed mixing barrel to obtain a premix;

[0034] S3: The premix is ​​conveyed into a twin-screw extruder through the main feed inlet of the twin-screw extruder, and the remaining glass fiber accounting for 4%-40% of the formula weight percentage is conveyed into the twin-screw extruder through the side feed inlet. All material components are melt-blended by screw shearing and extruded into granules to obtain the high-efficiency flame-retardant nylon composite material.

[0035] Preferably, the pre-drying condition in S2 is drying at 100° C. for 4 to 6 hours.

[0036] In the present invention, the glass fibers are fed sideways to improve the integrity of the glass fibers and ensure the strength of the products. Most of the glass fibers are fed sideways and are not mixed with the raw materials. A small amount of glass fibers mixed with the raw materials are fed through the main feeding channel, which is equivalent to two parts of glass fibers passing through different channels. The two parts of glass fibers have different functions. The former focuses on filling and strengthening, while the latter focuses more on synergistic dispersion and also plays a reinforcing role as a filler.

[0037] Preferably, the length-to-diameter ratio of the twin-screw extruder is (30-50):1, the rotation speed is 250-500 rpm, and the extrusion temperature is 200-260°C.

[0038] In a third aspect, the present invention provides the use of the above-mentioned high-efficiency flame-retardant nylon composite material in the preparation of plastic parts for electronic appliances.

[0039] After the high-efficiency flame-retardant nylon composite material product prepared by the present invention is injection molded into ISO specimens, tensile, bending and impact mechanical properties are tested according to ISO527, ISO178 and ISO179 standards. The tensile strength is ≥150Mpa, the bending strength is ≥180Mpa, and the cantilever beam notched impact strength is ≥10J / m 2, ISO2813 85° gloss ≥90, flame retardant performance tested according to UL-94 standard, reaching 0.8mm V0.

[0040] In a fourth aspect, the present invention provides a plastic part, which is made of the above-mentioned high-efficiency flame-retardant nylon composite material and at least one auxiliary material, wherein the auxiliary material includes but is not limited to: colorant, montmorillonite, talcum powder, and melamine.

[0041] In the prior art, organic phosphinates are used as halogen-free flame retardants and introduced into PA6 nylon resin. Under conventional mass production, due to the poor compatibility and dispersibility between organic phosphinates and nylon, the flame retardant efficiency is low and the flame retardant grade is unstable. Usually, the weight fraction of organic phosphinates is increased to improve the flame retardant effect. However, since the compatibility and dispersibility problems are not solved, the mechanical strength and toughness of the composite material will be reduced, the surface fiber floating is serious, and the processing fluidity is poor.

[0042] In the present invention, a small amount of PA66 is introduced into the system of PA6 as the main resin. PA66 can act as a nucleating agent, which can improve the crystallinity and its crystallization temperature, and promote the mechanical strength of the composite material. On this basis, the introduction of the commercial composite nucleating agent of Brüggemann can further effectively improve the crystallization efficiency of PA6, promote the composite material to absorb a large amount of heat during combustion, reduce its combustion temperature, that is, reduce the combustion efficiency. At the same time, the inventor found that the high-efficiency crystallization improves the diffuse reflection efficiency of the material, the surface of the composite material is smoother, and the appearance finish of the injection molded product is greatly improved.

[0043] Introducing semi-aromatic nylon (MXD6 or PA6T / 6I / 66) into the PA6-based resin system has a high crystallization temperature, fast crystallization rate, and good fluidity. It can quickly form a resin layer on the material surface, infiltrate and coat the glass fiber on the material surface, and improve the surface smoothness.

[0044] On the basis of having little effect on the viscosity (melt index) of the composite material, introducing a small amount of chain extender (a mixture of phorone diisocyanate and polyacrylic acid modified MXD6 chain extender) into the PA6-based resin system can effectively increase the molecular weight and molecular weight distribution of the PA6 molecule and produce micro-crosslinking, which effectively improves the mechanical strength of the composite material and greatly increases the difficulty of the composite material to liquefy and flow and form molten droplets and gaseous molecules during combustion, thereby greatly improving the flame retardant effect.

[0045] Introducing polyacrylic acid-modified MXD6 synergistic flame retardant into the PA6-based resin system can promote MXD6 to effectively form a carbon layer, greatly improving the flame retardant efficiency. After introducing a small amount of chain extender, MXD6 or PA6T / 6I / 66 can be grafted with PA6 molecules and grafted with polyacrylic acid-modified MXD6 synergistic flame retardant, further enhancing the carbonization ability of PA6 molecules during combustion. During combustion, a large amount of carbon layer is formed on the surface of the composite material, isolating external oxygen and thereby greatly improving the flame retardant effect.

[0046] Introducing the MXD6 release agent modified with polyacrylic acid ricinoleate into the PA6-based resin system can greatly improve the surface smoothness during the injection molding process, and the ricinoleate compounds can further improve the demoulding effect of the product; it can produce intermolecular hydrogen bonds and chemical grafting with the polyacrylic acid-modified MXD6 flame retardant and polyacrylic acid-modified MXD6 chain extender, further improving the carbonization efficiency on the surface of the composite material and improving the flame retardant effect.

[0047] When melt extruding to prepare high-gloss and double 85-resistant high-efficiency flame-retardant nylon composite materials, a small amount of glass fiber is mixed with flame retardants, resins, etc., and the main feed is melt-extruded and granulated through a screw. Due to the shearing effect of the glass fiber in the melt, the dispersibility of the organic phosphite in the melt can be greatly improved through physical dispersion, thereby greatly improving the flame retardant efficiency of the halogen-free flame-retardant nylon composite materials.

[0048] The beneficial effects of the present invention are as follows: the flame-retardant nylon composite material prepared by the preparation method of the present invention through synergistic flame retardancy, chain extension reaction, surface wetting, PA66 heterogeneous nucleation, glass fiber physical shearing and dispersion of flame retardant has high flame retardant efficiency (UL-94V0), good mechanical strength, smooth surface appearance, anti-aging performance, good processing fluidity, and is suitable for the field of electronic appliances. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is the test appearance picture of Example 1-3 and Comparative Example 1-5. DETAILED DESCRIPTION

[0050] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.

[0051] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0052] Sources of components in each embodiment and comparative example:

[0053] PA6 nylon, YH400, relative viscosity 2.4-2.6, Hunan Yuehua Co., Ltd.

[0054] PA66 nylon, ERP27, relative viscosity 2.6-2.7, Pingdingshan Shenma Co., Ltd.

[0055] Semi-aromatic nylon A1, MXD6, ZYMX-5001, relative viscosity 2.0-2.2, Sinochem International Co., Ltd.

[0056] Semi-aromatic nylon A2, PA6T / 6I / 66, T900, relative viscosity 0.5-2.5, Shanghai Beigang New Materials Co., Ltd.

[0057] Glass fiber, flatness ratio 3, short cut length 3mm, fiber diameter 10μm, ECS3F-03-568H, Jushi Group. 8-20

[0058] The halogen-free flame retardant is a mixture of organic phosphinate and its derivatives, melamine derivatives, and zinc borate, with a mass ratio of 8:5:5. Among them, organic phosphinate and its derivatives: Jiangsu Oupu New Materials Co., Ltd., model 331. Melamine derivatives: Budenheim, Germany, model 342. Zinc borate: Shandong Wuwei Flame Retardant Technology, model: ZB23-70.

[0059] The chain extender includes chain extender B1 and chain extender B2. According to detection, the number average molecular weight is 500-10000 g / mol, the melting point is 50-200° C., and the melt flow index measured at 250° C. / 2.16 kg according to ISO 1133-2011 is 0.05-200 g / 10 min.

[0060] Chain extender B1, phorone diisocyanate, BASF, IPDI.

[0061] Chain extender B2, a homemade polyacrylic acid modified MXD6 chain extender, is prepared by the following steps:

[0062] S1: Preparation of polyacrylic acid solution: Add 6% m-xylylenediamine and 15% acrylic acid into a reactor equipped with a stirring and condensation reflux device, put it into a constant temperature oil bath and heat it to 120°C, dissolve 5% benzoyl peroxide in 10% xylene, and drip it into the reactor. After reacting for 15 minutes, change the condensation reflux to condensation recovery, use the difference in boiling points to evaporate the xylene, and recycle it, finally obtaining a low molecular weight polyacrylic acid / m-xylylenediamine solution;

[0063] S2: Preparation of polyacrylic acid modified MXD6: Prepare 50wt% adipic acid suspension A and 60wt% meta-xylenediamine solution B respectively; obtain 60% carboxylic acid terminated intermediate ABA solution and 60% amine terminated intermediate BAB solution respectively in different dropwise addition orders; add the ABA solution into a reaction kettle with a stirring paddle, dropwise add the BAB solution into the ABA solution under stirring at 80°C, and add 20% low molecular weight polyacrylic acid / meta-xylenediamine solution, and add The pH value of m-phenylenediamine was adjusted to 7.0 to complete the reaction; MXD6 salt was configured into a 90wt% aqueous solution and put into a reactor, and the temperature was slowly raised to 210°C under a N2 atmosphere, and the reaction was carried out for 1 hour. After the pressure was released to normal pressure, the temperature was raised to 240°C, and the vacuum was drawn while maintaining the pressure between 0.07 and 0.03MPa. The temperature was gradually raised to 260°C, and the reaction was carried out for 1 hour. The material was discharged and dried in a vacuum box at 120°C for 2 hours, and then the temperature was raised to 140°C and dried for 8 hours to obtain a polyacrylic acid modified MXD6 chain extender.

[0064] Synergistic flame retardant, homemade polyacrylic acid modified MXD6 synergistic flame retardant, the preparation method comprises the following steps:

[0065] S1: Preparation of polyacrylic acid solution: Add 50% m-xylylenediamine and 15% acrylic acid into a reactor equipped with a stirring and condensation reflux device, put it into a constant temperature oil bath and heat it to 120°C, dissolve 5% benzoyl peroxide in 10% xylene, and drip it into the reactor. After reacting for 15 minutes, change the condensation reflux to condensation recovery, use the difference in boiling points to evaporate the xylene, and recycle it, finally obtaining a low molecular weight polyacrylic acid / m-xylylenediamine solution;

[0066] S2: Preparation of polyacrylic acid modified MXD6: 40 wt% adipic acid suspension A and 80 wt% meta-xylenediamine solution B were prepared respectively; 60% carboxylic acid terminated intermediate ABA solution and 60% amine terminated intermediate BAB solution were obtained respectively in different dropwise addition orders; the ABA solution was added into a reaction kettle with a stirring paddle, the BAB solution was added dropwise into the ABA solution under stirring at 80°C, and 5% low molecular weight polyacrylic acid / meta-xylenediamine solution was added, and the intermediate BAB solution was added by adding the meta-xylenediamine solution. The pH value was adjusted to 7.0 with diphenylamine to complete the reaction; MXD6 salt was prepared into an 80wt% aqueous solution and put into a reactor. Under a N2 atmosphere, the temperature was slowly raised to 210°C, the reaction was carried out for 1 hour, the pressure was released to normal pressure, the temperature was raised to 240°C, vacuumed and the pressure was maintained between 0.07-0.03MPa, the temperature was gradually raised to 260°C, the reaction was carried out for 1 hour, the material was discharged, and the material was dried at 120°C in a vacuum box for 2 hours, and the temperature was raised to 140°C and dried for 8 hours to obtain a polyacrylic acid modified MXD6 synergistic flame retardant.

[0067] The test shows that the number average molecular weight is 500-10000 g / mol, the melting point is 50-200°C, and the melt flow index measured at 250°C / 2.16 kg according to ISO 1133-2011 is 0.05-200 g / 10 min.

[0068] A release agent, a self-made MXD6 release agent modified with polyacrylic acid ricinoleate, wherein the preparation method comprises the following steps:

[0069] S1: Preparation of polyacrylic acid solution: Add 70% ricinoleic acid and 20% acrylic acid into a reactor equipped with a stirring and condensation reflux device, put it into a constant temperature oil bath and heat it to 120°C, dissolve 5% benzoyl peroxide in 20% xylene, and drip it into the reactor. After reacting for 15 minutes, change the condensation reflux to condensation recovery, use the difference in boiling points to evaporate the xylene, and recycle it, finally obtaining a low molecular weight polyacrylic acid / ricinoleic acid solution;

[0070] S2: Preparation of polyacrylic acid modified ricinoleate: cooling to 85°C, adding 10% phorone diisocyanate, reacting for 5 hours under N2 atmosphere, and adjusting the viscosity of the system by adding m-xylylenediamine to finally obtain polyacrylic acid ricinoleate;

[0071] S3: Preparation of polyacrylic acid ricinoleate-modified MXD6: Prepare 50wt% adipic acid suspension A and 80wt% meta-xylenediamine solution B respectively; obtain 60% carboxylic acid-terminated intermediate ABA solution and 60% amine-terminated intermediate BAB solution respectively under different dropwise addition orders; add the ABA solution into a reactor with a stirring paddle, dropwise add the BAB solution into the ABA solution under stirring at 80°C, and add 80% polyacrylic acid ricinoleate; by adding meta-xylenediamine, The pH value was adjusted to 7.5 with amine to complete the reaction; the MXD6 salt was configured into a 90wt% aqueous solution and put into the reactor, and the temperature was slowly raised to 210°C under N2 atmosphere, and the reaction was carried out for 1 hour. After the pressure was released to normal pressure, the temperature was raised to 240°C, and the vacuum was drawn while maintaining the pressure between 0.07 and 0.03MPa. The temperature was gradually raised to 260°C, and the reaction was carried out for 1 hour. The material was discharged and dried in a vacuum box at 120°C for 2 hours, and then the temperature was raised to 140°C and dried for 8 hours to obtain a polyacrylate ricinoleate-modified MXD6 release agent.

[0072] The test shows that the number average molecular weight is 500-10000 g / mol, the melting point is 50-260°C, and the melt flow index measured at 250°C / 2.16kg according to ISO 1133-2011 is 0.05-200 g / 10min.

[0073] Nucleating agent, Brüggemann, Germany, P22.

[0074] Processing aids include antioxidants and lubricants, with the mass ratio of the two being 4:5.

[0075] Antioxidant 1098 / 168, Tianjin Lianlong New Materials Co., Ltd., model RIANOX 168 / 1098.

[0076] Lubricant PETs, Lonza, USA, PETS-P.

[0077] Examples 1-3 and Comparative Examples 1-5

[0078] The components and weight proportions of the flame-retardant nylon composite materials of Examples 1-3 and Comparative Examples 1-5 are shown in Table 1.

[0079] Table 1 Components and weight proportions of flame retardant nylon composite materials of Examples 1-3 and Comparative Examples 1-5

[0080]

[0081] The preparation method of the flame retardant composite material of Examples 1-3 and Comparative Examples 1-5 comprises the following steps:

[0082] After the mixed materials to be mixed are mixed evenly, they are placed in the main feed and melt-extruded, cooled and granulated according to fixed feeding frequency, screw speed and extrusion temperature to obtain a flame-retardant composite material.

[0083] The length-to-diameter ratio of the twin-screw extruder is 30-50:1, the rotation speed is 250-500rpm, and the extrusion temperature is 200-260°C.

[0084] Experimental Results

[0085] In order to verify the performance of the flame retardant composite material of the present invention, the products of each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:

[0086] (1) Glossiness test: the flame-retardant composite materials of the embodiment and the standard example were injection molded into standard color plates, and the glossiness of the color plates was tested using a gloss meter (the angle was selected to be 85°);

[0087] (2) Flame retardant performance test: the flame retardant composite materials of the embodiment and the standard example were injection molded into UL flame retardant specimens and tested according to the UL94 standard;

[0088] (3) Appearance test: The flame-retardant composite materials of the embodiment and the standard example were injection molded into standard color plates, and 16-20 molds were taken for continuous injection molding to evaluate the appearance grade. Appearance grade determination: Grade 1 has no obvious floating fibers, Grade 2 has a small amount of floating fibers, Grade 3 has serious floating fibers, and Grade 4 has a large amount of floating fibers.

[0089] (4) Precipitation test: The flame retardant composite materials of the embodiment and the standard example were injection molded into a standard shrink plate color plate, and the injection molding was continued. A 16-20 mold was taken and placed at 85°C and 85 humidity for 1000 hours (double 85 test). The appearance grade was evaluated again. Appearance grade judgment: Grade 1 has no obvious precipitation, Grade 2 has a small amount of precipitation, Grade 3 has obvious precipitation, and Grade 4 has a large amount of precipitation.

[0090] (5) Toughness test: The flame retardant composite materials of the embodiment and the standard example were injection molded into standard specimens, and impact mechanical properties were tested according to ISO 179 standard.

[0091] The test results are shown in Table 2.

[0092] Table 2 Test results

[0093] sample Flame retardant grade Glossiness (85°) Floating fiber grade Impact performance Barrier properties Example 1 0.8V0 92 1 11.6 1 Example 2 0.8V0 95 1 11.9 1 Example 3 0.8V0 95 1 12 2 Comparative Example 1 1.6V1 35 5 7.5 5 Comparative Example 2 0.8V1 80 2 8.5 2 Comparative Example 3 0.8V1 85 2 9.7 2 Comparative Example 4 1.6V0 80 2 10.5 2 Comparative Example 5 0.8V1 81 2 10.9 2

[0094] From Table 2, Figure 1 It can be seen that when the technical solution of the present invention is adopted, the flame retardant composite material obtained has a flame retardancy of V0 at 0.8 mm, a glossiness of greater than 90 at 85°, an impact resistance greater than 10, and a smooth appearance without floating fibers.

[0095] From Comparative Examples 1-2, it can be seen that on the basis of similar total amount of nylon, a small amount of PA6 is replaced by PA66, MXD6 and a small amount of composite nucleating agent and glass fiber are introduced into the pre-blend, and the melt-extruded flame-retardant composite material has excellent flame retardant properties and appearance smoothness.

[0096] From the comparison of Example 1 and Comparative Examples 3-5, it can be seen that, based on Comparative Example 2, the introduction of an appropriate amount of synergistic flame retardant and chain extender can effectively improve the flame retardant properties, impact properties, appearance smoothness, and anti-precipitation properties of the flame retardant composite material, and reduce the amount of organic hypophosphite flame retardant by at least 80%, effectively reducing the cost.

[0097] From the comparison of Examples 2-3 and Comparative Examples 1-5, it can be seen that, based on Example 1, the introduction of an appropriate amount of release agent can effectively improve the surface gloss of the flame-retardant composite material and improve the flame retardant effect, so that the composite material has excellent flame retardant properties, impact resistance, appearance smoothness and anti-precipitation performance.

[0098] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A high-gloss, double 85-resistant, high-efficiency flame-retardant nylon composite material, characterized by: Calculated by weight percentage, it includes the following components: 40%-80% PA6 nylon, 2%-10% PA66 nylon, 2%-10% semi-aromatic nylon, 5%-50% glass fiber, 8%-20% halogen-free flame retardant, 1%-10% synergistic flame retardant, 0.2%-5% chain extender, 0.2%-1% release agent, and 0.2%-1% nucleating agent.

2. The high-efficiency flame-retardant nylon composite material according to claim 1, characterized in that: The halogen-free flame retardant is a mixture of organic phosphinate and its derivatives, melamine derivatives and zinc borate, and the percentages of the total weight of the composite material are 8%-20%, 0-7% and 0-7% respectively.

3. The high-efficiency flame-retardant nylon composite material according to claim 1, characterized in that: The semi-aromatic nylon is PA6T / 6I / 66 or MXD6.

4. The high-efficiency flame-retardant nylon composite material according to claim 1, characterized in that: The high-efficiency flame-retardant nylon composite material also includes 0.5%-4% of processing aids, and the processing aids include antioxidants and lubricants.

5. The high-efficiency flame-retardant nylon composite material according to claim 1, characterized in that: The synergistic flame retardant is a polyacrylic acid-modified MXD6 synergistic flame retardant, and the preparation method thereof comprises the following steps: S1: preparing a polyacrylic acid solution: adding 40%-80% m-xylenediamine and 10%-20% acrylic acid to a reaction kettle equipped with a stirring and condensation reflux device, placing the kettle in a constant temperature oil bath and heating it to 120°C, dissolving 0.1%-5% benzoyl peroxide in 5%-20% xylene, and dripping it into the reaction kettle. After a certain reaction time, changing the condensation reflux to condensation recovery, utilizing the difference in boiling points to evaporate the xylene, and recycling it, finally obtaining a low molecular weight polyacrylic acid / m-xylenediamine solution; S2: Preparation of polyacrylic acid modified MXD6: Prepare 30%-50% adipic acid suspension A and 60%-80% meta-phenylenediamine solution B respectively; obtain 40%-60% carboxylic acid terminated intermediate ABA solution and 40%-60% amine terminated intermediate BAB solution respectively in different dropwise addition orders; add the ABA solution into a reaction kettle with a stirring paddle, drop the BAB solution into the ABA solution under stirring at 80°C, and add 1%-10% low molecular weight polyacrylic acid / meta-phenylenediamine solution; The dimethylamine solution is adjusted to pH 7.0-7.5 by adding meta-phenylenediamine to finally complete the reaction; MXD6 salt is configured into a 60%-90% aqueous solution and put into a reactor, and the temperature is slowly raised to 210°C under a N2 atmosphere. After the reaction is completed, the pressure is released to normal pressure, the temperature is raised to 240°C, and the pressure is evacuated and maintained between 0.07-0.03MPa, and the temperature is gradually raised to 260°C. After the reaction is completed, the material is discharged and dried at high temperature in a vacuum box to obtain the polyacrylic acid modified MXD6 synergistic flame retardant.

6. The high-efficiency flame-retardant nylon composite material according to claim 1, characterized in that: The chain extender is a mixture of phorone diisocyanate and polyacrylic acid modified MXD6 chain extender, wherein the phorone diisocyanate accounts for 0.1%-2.5% of the total weight of the composite material. The preparation method of the polyacrylic acid modified MXD6 chain extender comprises the following steps: S1: preparing a polyacrylic acid solution: adding 40%-80% m-xylenediamine and 10%-20% acrylic acid to a reaction kettle equipped with a stirring and condensation reflux device, placing the kettle in a constant temperature oil bath and heating it to 120°C, dissolving 0.1%-5% benzoyl peroxide in 5%-20% xylene, and dripping it into the reaction kettle. After a certain reaction time, changing the condensation reflux to condensation recovery, utilizing the difference in boiling points to evaporate the xylene, and recycling it, finally obtaining a low molecular weight polyacrylic acid / m-xylenediamine solution; S2: Preparation of polyacrylic acid modified MXD6: Prepare 30%-50% adipic acid suspension A and 60%-80% m-xylenediamine solution B respectively; obtain 40%-60% carboxylic acid terminated intermediate ABA solution and 40%-60% amine terminated intermediate BAB solution respectively in different dropwise addition orders; add the ABA solution into a reaction kettle with a stirring paddle, dropwise add the BAB solution into the ABA solution under stirring at 80°C, and add 5%-20% low molecular weight polyacrylic acid / m-xylenediamine solution; The benzylenediamine solution is adjusted to pH 7.0-7.5 by adding meta-xylylenediamine to finally complete the reaction; MXD6 salt is configured into a 60%-90% aqueous solution and put into a reaction kettle, and the temperature is slowly raised to 210° C. under a N2 atmosphere. After the reaction is completed, the pressure is released to normal pressure, the temperature is raised to 240° C., and the pressure is evacuated and maintained between 0.07 and 0.03 MPa, and the temperature is gradually raised to 260° C. After the reaction is completed, the material is discharged and dried at high temperature in a vacuum box to obtain the polyacrylic acid modified MXD6 chain extender.

7. The high-efficiency flame-retardant nylon composite material according to claim 1, characterized in that: The release agent is a MXD6 release agent modified with polyacrylic acid ricinoleate, and the preparation method thereof comprises the following steps: S1: preparing a polyacrylic acid solution: adding 40%-70% ricinoleic acid and 10%-20% acrylic acid to a reactor equipped with a stirring and condensation reflux device, placing the reactor in a constant temperature oil bath and heating the temperature to 120°C, dissolving 0.1%-5% benzoyl peroxide in 5%-20% xylene, and dripping the mixture into the reactor. After a certain reaction time, changing the condensation reflux to condensation recovery, using the difference in boiling points to evaporate the xylene, and recycling it, finally obtaining a low molecular weight polyacrylic acid / ricinoleic acid solution; S2: Preparation of polyacrylic acid modified ricinoleate: cooling to 85°C, adding 1%-10% phorone diisocyanate, reacting under N2 atmosphere, and adjusting the viscosity of the system by adding m-xylylenediamine to finally obtain polyacrylic acid ricinoleate; S3: Preparation of MXD6 modified with polyacrylic acid ricinoleate: prepare 30%-50% adipic acid suspension A and 60%-80% m-xylenediamine solution B respectively; obtain 40%-60% carboxylic acid-terminated intermediate ABA solution and 40%-60% amine-terminated intermediate BAB solution respectively in different dropwise addition orders; add the ABA solution into a reaction kettle with a stirring paddle, drop the BAB solution into the ABA solution under stirring at 80°C, and add 10%-100% polyacrylic acid ricinoleate; Oleic acid ester, by adding meta-phenylenediamine to adjust the pH to 7.0-7.5, and finally complete the reaction; MXD6 salt is configured into a 60%-90% aqueous solution and put into a reactor, and slowly heated to 210°C under N2 atmosphere. After the reaction is completed, the pressure is released to normal pressure, and the temperature is increased to 240°C, and vacuum is drawn and the pressure is maintained between 0.07-0.03MPa, and the temperature is gradually increased to 260°C. After the reaction is completed, the material is discharged and dried at high temperature in a vacuum box to obtain the polyacrylic acid ricinoleate modified MXD6 release agent.

8. A method for preparing a high-gloss, double 85-resistant, high-efficiency flame-retardant nylon composite material, characterized in that: The following steps are involved: S1: According to weight percentage, weigh 40%-80% of PA6 nylon, 2%-10% of PA66 nylon, 2%-10% of semi-aromatic nylon, 5%-50% of glass fiber, 8%-20% of halogen-free flame retardant, 1%-10% of synergistic flame retardant, 0.2%-5% of chain extender, 0.2%-1% of release agent, and 0.2%-1% of nucleating agent; S2: pre-dry the three resins of PA6 nylon, PA66 nylon and semi-aromatic nylon in S1 respectively, and then pre-mix the glass fiber accounting for 1% to 10% of the weight percentage of the formula with PA6 nylon, PA66 nylon, semi-aromatic nylon, halogen-free flame retardant, synergistic flame retardant, chain extender, release agent and nucleating agent through a high-speed mixing barrel to obtain a premix; S3: The premix is ​​conveyed into a twin-screw extruder through the main feed inlet of the twin-screw extruder, and the remaining glass fiber accounting for 4%-40% of the formula weight percentage is conveyed into the twin-screw extruder through the side feed inlet. All material components are melt-blended by screw shearing and extruded into granules to obtain the high-efficiency flame-retardant nylon composite material.

9. Use of the high-efficiency flame-retardant nylon composite material according to any one of claims 1 to 7 in the preparation of plastic parts for electronic appliances.

10. A plastic part, characterized in that: The plastic component is made of the high-efficiency flame-retardant nylon composite material according to any one of claims 1 to 7 and at least one auxiliary material.

Citation Information

Patent Citations

  • High-gloss low-warp halogen-free flame-retarded polyamide and preparation method thereof

    CN104448801A

  • Seat stool in elevator car

    CN109552968A

  • Glass fiber reinforced nylon material used for extrusion molding, preparation method and application

    CN103242649A

  • Low-color-difference fiber-added nylon and forming process thereof

    CN112625429A

  • Fatigue-resistant high-gloss nylon heat insulation strip flame-retardant material and preparation method thereof

    CN114773836A

Cited By

  • Electroplatable high-temperature-resistant nylon composite material and preparation method thereof

    CN120173401A